2083. HIV Testing Rates in NC Emergency Departments Before and During Covid Mitigation. (15th December 2022) - Leonard, Michael; Thomas, Jeremy; Tapp, Hazel; Ludden, Thomas
Abstract: Background: During the early stages of the COVID-19 pandemic, non-emergent services were limited or suspended in multiple ways. Restrictions in primary care may have limited STI testing, such as HIV, where timely access to testing and care is critical to mitigation efforts. Conversely, Emergency Departments (ED) operated with fewer restrictions and more in-person options. Even though patient census numbers decreased in some areas from those seen pre-covid lockdown, EDs and hospitals often became overwhelmed with patients seeking care for both severe acute illness but just importantly services that might normally have been received in outpatient settings. Methods: Observational study of HIV screening year-over-year in four EDs that are part of a large healthcare system located in the Southeast. Screenings of individuals 18 and over seen in the EDs were normalized per 1000 patients. Rates were also compared to two primary care clinics, located in the same metropolitan area, serving mainly Medicaid and uninsured patients. Results: From March 2019 through February 2020 there were 33.47 tests per 1000 patients at two community clinics and 7.79 tests per 1000 patient at four EDs located in the same region during that span. From March 2020 to February 2021, screening numbers in the primary care clinics dropped to an average of 22.7/1000; however, screenings in the ED remained stable and slightly increased to 10.7/1000. From March 2021 to February 2022, screenings in the primary care clinics returned to an average 36.9/1000 with screenings in the ED still above pre-covid levels at 9.48/1000. These trends in the ED screening remained consistent across gender, race, and ethnicity. Patient census at four ED sites located in the southwestern region of North Carolina dropped significantly during the first year of physical distancing covid-19 mitigation measures when compared to the two years prior. These census numbers increased during the second year of covid-19 but failed to return to previous levels. During the first year of physical distancing covid-19 mitigation measures HIV testing rates in the emergency department remained constant, and even increased in more urban areas, despite the significant decrease in overall patient census. Conclusion: With the observation that HIV screening decreased in primary care settings during the beginning of the covid-19 pandemic, there exists the possibility that new HIV infections may yet remain undiagnosed. That HIV testing remained constant in the ED, however, reinforces the importance of having embedded procedures in place for screening and linking both newly positive and at-risk patients into care to help mitigate the HIV epidemic. Disclosures: All Authors : No reported disclosures.